UTILIZATION OF THE DIENG TEMPLE SITE AS HISTORICAL RESOURCES TO INCREASE HISTORICAL COMPREHENSION STUDENTS (CLASSROOM ACTION RESEARCH IN PUBLIC HIGH SCHOOL 1 WONOSOBO) - Kartikasari, Diah Ayu (Universitas Pendidikan Indonesia, 2017)
Dieng Temple site in the highlands of Central Java has not been used as a source of learning history. The site can be used to bring learners closer to their environment. This study aims to improve the historical comprehension of learners through the use of Dieng Temple site as a source of historical learning. This research is a Classroom Action Research in Public High School 1 Wonosobo. Data were collected by observation, inter-view and documentation. The results showed that the learning process of history through Dieng Temple site can provide the ability to learners to interpret the literal meaning of Dieng Temple by using their own language. This makes students able to understand the history of existing sites in the Dieng area. Understanding the history has been raising awareness of learners to take part in maintaining the sustainability of Dieng temple site.